2019
DOI: 10.1111/ggi.13630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of kidney transplantation in older end‐stage renal disease patients: A nationwide cohort study

Abstract: Aim The aim of the present study was to investigate the clinical outcomes of kidney transplantation (KT) in elderly recipients compared with those in young recipients. Methods We compared the incidence of biopsy‐proven acute rejection, death‐censored allograft survival and all‐cause mortality, and also compared the impact of high sensitization or desensitization on the clinical outcomes of elderly and young recipients. Results A total of 4966 KT recipients from the Korean Organ Transplantation Registry were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…In our study long-term patient and graft survival were significantly worse in the elderly group, but death-censored graft survival did not differ in the elderly, which indicates that most of the EKT deaths occurred while the recipient still had the functioning graft. The same observation was done in other studies, there was no difference in death censored allograft survival in patients following deceased donor kidney transplantation aged >60 and <60 years [17] …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study long-term patient and graft survival were significantly worse in the elderly group, but death-censored graft survival did not differ in the elderly, which indicates that most of the EKT deaths occurred while the recipient still had the functioning graft. The same observation was done in other studies, there was no difference in death censored allograft survival in patients following deceased donor kidney transplantation aged >60 and <60 years [17] …”
Section: Discussionsupporting
confidence: 83%
“…The same observation was done in other studies, there was no difference in death censored allograft survival in patients following deceased donor kidney transplantation aged >60 and <60 years. [17] The elderly population is underrepresented in published studies, and we believe that our unique methodological approach may at least modestly contribute to filling the existing gaps in knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, most studies on the risk of desensitization treatment have been short-term studies; hence, the impact of the longterm risk of desensitization treatment remains unclear. Inconsistent results have been reported on the effect of desensitization treatment on infection risk [91][92][93][94]. Kahwaji et al [93] reported that there were no differences in bacterial, viral, and fungal infection rates between the rituximab with high-dose IVIG group and the non-administered group over 18 months after transplantation.…”
Section: Allograft and Patient Outcomesmentioning
confidence: 99%
“…Care needs of renal transplant recipients are influenced by their demographic data (e.g., sex and age) and specific disease characteristics (Costa‐Requena et al, 2017a; Ko et al, 2019). Recipients are eager to receive disease‐specific care and instructions because their needs vary based on side effects and adherence with immunosuppressive medication (Been‐Dahmen et al, 2018; Leite et al, 2018; Luk, 2004), living or deceased donor (Ko et al, 2019; Zimmermann, Pabst, Bertram, Schiffer, & de Zwaan, 2016), time since transplantation (Antunes et al, 2018; Been‐Dahmen et al, 2018), complications or organ rejection occurrence and recurrence of the primary disease (Bicalho et al, 2019). The high unmet needs were significantly associated with decreased quality of life, self‐reported health status and increased symptom burden (Ko, 2016), anxiety (Chen, Weng, & Lee, 2010) and depression (Park, Park, Oh, & Cho, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%